Vigna radiata extracts in pumpkin and soya bean oil: A novel therapeutic approach for Alzheimer’s disease - Haroon Amin; Shazia Anwer Bukhari; Zunera Chauhdary; Naheed Akhter; Maria Saleem (PLoS ONE, 2025)
Vigna radiate also known as mung beans, contains various bioactive compounds like polyphenols, flavonoids, and saponins. V. radiata therapeutic potential is enhanced by preparation of its extract in Pumpkin oil and soya bean oil by enrichment of bioactive compounds holding antioxidant, anti-inflammatory, and neuro-protective properties. The research study was aimed was to explore the healing endeavors of V. radiate pumpkin and soya bean oil extract in rectification of neuro-motor dysfunction and mental health decline in Alzheimer’s disease (AD) rat model. After preliminary physico-phytochemical characterization and GC-MS analysis, AD model was established by administration of oral D-galactose and aluminum chloride 150 mg/kg each for 42 days daily. V. radiate extract in pumpkin and soya bean oil at doses 250 and 500 mg/kg was administered and rivastigmine (3 milligrams per kilogram) to treatment animals. To determine the cognitive decline and neuro-coordination dysfunctions behavioral tests were performed along with biochemical, neurochemical and histopathological analysis. ELISA and real time polymerase chain reaction were carried out to estimate the expression of tumor necrosis factor-α, Interleukine-6 and mRNA expression of neurodegenerative biomarkers. Gas chromatography Mass Spectrometry findings revealed the existence of favorable amount of neuro-defensive bioactive compounds in both oil extracts.V. radiate pumpkin and soya bean oil extract dose proportionally alleviated the behavioral dysfunctions, modulated the first line antioxidant enzymes and neurotransmitters s’ level with anticholinesterase pursuits. The mRNA expression of AChE, IL-1β, TNF-α, IL-1α and β secretase were downregulated by these extracts treatment. V. radiate oil extracts also modulated the neuro-inflammatory protein expression and histopathological hallmarks in AD model animals. Therefore, it is purposed that V. radiate enriched extract in pumpkin and soya bean oil could be used to treat AD like memory dysfunction and motor symptoms.